SPH numerical and physical modeling of wave overtopping a porous breakwater - Didier, E. (2014)
Numerical modeling of an entire physical wave flume with a breakwater at scale 1:30 was performed using a coupling technique between FLUINCO wave propagation and SPHyCE wave-structure interaction codes. The rock blocks of the breakwater are directly simulated with the SPHyCE code using similar rectangular blocks. Numerical results of free surface elevation before the breakwater, over and inside the rock armor layer and overtopping discharge over the structure, for wave period 12s and wave heights 2.5 and 3.3m (prototype values), are in good accordance with experimental data.